The Impact of Blended Learning an Educational Innovation as on Student Character Building in Islamic Religious Education - Salim Salim; Mohamad Aji Prasetia; Muhammad Bagas F.; Fatkhur Rohman; Abdurrahman Abdurrahman (Qubahan Academic Journal)
Technological developments are thought to be capable of bringing about changes in various aspects, including education. We have implemented various technologically-driven educational innovations to enhance the quality of education and accomplish educational objectives. One aspect of innovation in education is the implementation of a mixed learning system, also known as hybrid learning, is one aspect of education innovation. The goal of this research is to assess how blended learning, an educational innovation, impacts students' affective abilities, particularly their self-actualization and self-efficacy in Islamic religious education. Islamic religious education aims to instill a type of character education in students, making the implementation of educational innovation in the form of new conceptual mechanisms for learning crucial. The goal is to capture students' attention and achieve more quantifiable religious learning goals through character education. We conducted this research at MAN Medan School, which has a student population of 720. We used the Slovin method for the sampling technique, resulting in a random sample of 258 students. We used the confirmatory factor analysis method to test the research variables. The research results indicate that blended learning positively impacts self-efficacy, with a critical ratio of 8.282 and a significance level exceeding 1.96 at a significance level of 5%. Meanwhile, blended learning has a positive influence on self-actualization with a critical ratio of 3.323 and a significance level of the critical ratio above 1.96 with a significance level of 5%.